Development of Interactive PowerPoint Teaching Materials Based on Open-Ended Problems to Improve Students' Problem-Solving Skills in Mathematics Content for Grade V Elementary School - Dewa Ayu Bintang Kartika; Gusti Ngurah Sastra Agustika; I Wayan Sujana (Universitas Pendidikan Ganesha, 2025)
The lack of creativity in utilizing instructional media has contributed to students’ low problem-solving ability, particularly in the topic of fractions. As a result, students’ learning outcomes have not reached the desired level. This study aims to examine the effectiveness of interactive PowerPoint-based teaching materials integrated with open-ended problems in enhancing students' mathematics learning outcomes. This research employs a Research and Development (R&D) design using the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The study involved 24 fifth-grade students as research subjects. Data were collected using a learning achievement test and analyzed through normality, homogeneity, and t-tests. The normality test showed that the data were normally distributed, with Dmax values of 0.104 (pre-test) and 0.193 (post-test), both below the Dtable value of 0.269. The homogeneity test yielded an Fcount of 1.119 < Ftable 4.050, indicating homogeneous samples. The t-test showed a significant difference between pre-test and post-test results, with a tcount of 9.851 > ttable 2.069. These findings indicate that the use of interactive media based on open-ended problems is effective in improving students' mathematics learning outcomes. This suggests that such media development can serve as an innovative alternative in mathematics instruction.